Chemical Composition and Antibacterial Activity of Essential Oil Hyptis suaveolens (L.) Poit. (Lamiaceae) from the Venezuelan Plains - Ríos Tesch, Nurby (2015)
The essential oil (EO) obtained from the leaves and flowers of Hyptis suaveolens (L.) Poit. collected from Guasdualito, Apure State, Venezuela. Oil was obtained by hydrodistillation using a Clevenger trap. The oil was analyzed by gases chromatography-mass spectrometry (GC/MS). Thirty-five compounds were identified in the leaves (91.9% of the sample) and thirty compounds in the flowers (97.0% of the sample), the major compounds: 1,8-cineole (19.1% leaves, flowers 13.3%), fenchone (18.5% leaves, flowers 16.1%), bicyclogermacrene (12.7% leaves, flowers 18.8%), D-germacrene (6.3% leaves, flowers 10.0%). The antibacterial activity was evaluated by the agar diffusion method with disks against Staphylococcus aureus ATCC 25923, Enterococcus faecalis ATCC 29212, Escherichia coli ATCC 25922, ATCC 23357 Klebsiella pneumoneae, Salmonella typhi CDC 57, Pseudomonas aeruginosa ATCC 27853. Both EO inhibited the development of E. coli, K. pneumoneae, and S. typhi, with a minimun inhibitory concentration (MIC) ranging between 300 μL/mL and 450 μL/mL. These results represent a contribution to the study of the EO of H. suaveolens, besides it the first report on the antibacterial activity of the EO obtained from flowers of this specie.